2007
DOI: 10.2320/matertrans.maw200734
|View full text |Cite
|
Sign up to set email alerts
|

Mechanical Properties of Co-Based L1<SUB>2</SUB> Intermetallic Compound Co<SUB>3</SUB>(Al,W)

Abstract: Mechanical properties of L1 2 -Co 3 (Al,W) polycrystalline sample are investigated by compression testing at various temperature ranging from room temperature to 1193 K. It was found that at room temperature the 0.2% flow stress is 410 MPa and the compressive ductility is higher than 10%, whereas at 1193 K the 0.2% flow stress is 382 MPa and the compressive ductility is about 10%. Two candidates for the reaction scheme of the Co-rich region of the Co-Al-W ternary phase diagram are proposed by combining the res… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
46
0
1

Year Published

2011
2011
2015
2015

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 92 publications
(51 citation statements)
references
References 28 publications
(34 reference statements)
4
46
0
1
Order By: Relevance
“…Several recent Calphad thermodynamic assessments have been performed assuming c¢ is an equilibrium phase at 900°C. [2,[7][8][9] Other work has focused on the mechanical properties of ternary and higher order alloys, [10][11][12][13][14][15][16][17] the evolution and coarsening behavior of two-phase c-c¢ microstructure, [13,15,[18][19][20] or the microstructure and partitioning behavior of quaternary and higher order alloying elements. [13,15,[21][22][23][24][25] Furthermore, the only experimental data available for temperatures other than 900°C are the 1000°C isothermal section presented by Sato et al [1] and data reported by Xue et al at 1300°C.…”
Section: Introductionmentioning
confidence: 99%
“…Several recent Calphad thermodynamic assessments have been performed assuming c¢ is an equilibrium phase at 900°C. [2,[7][8][9] Other work has focused on the mechanical properties of ternary and higher order alloys, [10][11][12][13][14][15][16][17] the evolution and coarsening behavior of two-phase c-c¢ microstructure, [13,15,[18][19][20] or the microstructure and partitioning behavior of quaternary and higher order alloying elements. [13,15,[21][22][23][24][25] Furthermore, the only experimental data available for temperatures other than 900°C are the 1000°C isothermal section presented by Sato et al [1] and data reported by Xue et al at 1300°C.…”
Section: Introductionmentioning
confidence: 99%
“…Based on the equilibrium phase diagram, with the -liquidus at this composition estimated at 1496 K, direct solidification to primary should have become possible for undercoolings in excess of 53 K. However, despite obtaining the required undercooling, Ahmad et al were unable to obtain single-phase -Ni 3 Si. Instead, at all undercoolings, the solidification was always to a lamellar eutectic structure of singlephase -Ni 31 Si 12 and an Ni-rich lamellar consisting of a fine, eutectoid dispersion of -Ni and 1 . In addition, for undercoolings in excess of 132 K small amounts of the high temperature 3 -phase were observed uniformly dispersed throughout the sample.…”
Section: Ni 2 Si Is Not Considered Further As It Is Not Observed In Tmentioning
confidence: 99%
“…The solidification of intermetallic compounds such as Ni 3 Si, Ni 3 Al and Ni 3 Fe has attracted significant interest due to their attractive mechanical properties [1]; e.g. -Ni 3 Si displays a high melting point, excellent oxidation resistance and high strength at elevated temperatures.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Indeed, two-phase microstructures that resemble those in Ni-base superalloys have been proved to form in Co-Al-W based alloys through higher-order alloying additions [7,9]. However, almost nothing is known about the mechanical properties of the constituent L1 2 phase, Co 3 (Al,W) [10][11][12]. The L1 2 -ordered intermetallic compound, Co 3 (Al,W) is expected to exhibit physical properties similar to those exhibited by Ni 3 Al-based compounds that are the constituent phase of Ni-base superalloys.…”
Section: Introductionmentioning
confidence: 99%